Implementasi Manajemen Proyek Pembuatan Sistem Informasi Peminjaman Dokumen Perusahaan Dengan Metode Waterfall - Nugraha, Nunu Ariya; Fadilah, Defi Nur; Sutrisno, Sutrisno (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
This research explores the implementation of project management using the Waterfall method in the context of creating a company document lending information system. The main objective is to improve the efficiency and effectiveness of the document lending process through structured project planning, organization, and supervision. The method for creating this document lending application uses the Waterfall method. This method is used to create a document lending application in stages based on work starting with analysis, design, coding, and testing. The results are expected to provide practical guidance for organizations in adopting the Waterfall method for similar projects, as well as strengthen project management as a strategic tool for achieving corporate goals. Keywords: Manajemen Proyek, Waterfall, Website Aplikasi